The Preliminary Study on the Perception of Engineering Students on Blended Learning - Low M.C.; Lee C.K.; Sidhu M.S.; Hasan Z.; Lim S.P.; Lim S.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dynamics; Education computing; Failure analysis; Visualization; Blended learning; Complex engineering; Descriptive statistics; Learning difficulties; Online platforms; Pilot studies; Positive attitude; Student perceptions; Students